Fracture Propagation Characteristic and Micromechanism of Rock-Like Specimens under Uniaxial and Biaxial Compression - Xue-wei Liu; Quan-sheng Liu; Shi-bing Huang; Lai Wei; Guang-feng Lei (Shock and Vibration)
This paper presents a set of uniaxial and biaxial compression tests on the rock-like material specimens with different fracture geometries through a rock mechanics servo-controlled testing system (RMT-150C). On the basis of experimental results, the characteristics of fracture propagation under different fracture geometries and loading conditions are firstly obtained. The newly formed fractures are observed propagating from or near the preexisting crack tips for different specimens, while the propagation paths are affected by the loading condition obviously. Then, by adopting acoustic emission (AE) location technique, AE event localization characteristics in the process of loading are investigated. The locations of AE events are in good agreement with the macroscopic fracture propagation path. Finally, the micromechanism of macroscopic fracture propagation under uniaxial and biaxial compression conditions is analyzed, and the fracture propagation can be concluded as a result of microdamage accumulation inside the material. The results of this paper are helpful for theory and engineering design of the fractured rock mass.